2015
DOI: 10.21236/ad1002567
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Minimization and Management of Variability in Long Term Groundwater Monitoring Results

Abstract: The purpose of this project was to: 1) validate sample collection methods and procedures that minimize variability in groundwater monitoring results; and 2) validate improved methods to optimize monitoring frequency and assess long-term concentration trends that better account for short-term variability in groundwater monitoring results. All three objectives of the project were met. The demonstration results indicated that the sample method (except active no purge) has only a modest impact on monitoring variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Finally, it should be noted that uncertainties inherent in the SZNA rate estimation are difficult to quantify. This reflects uncertainties in all of the measured quantities used in the discharge calculations, especially errors in concentration data (up to 30%; McHugh et al ), errors in hydraulic conductivity measurement (2× to 10×), errors in measurement of hydraulic gradient (2×), differences in results for different data interpolation methods (log, linear, nearest neighbor; 2× to 5×), and uncertainty related to the spatial resolution (sampling density) of transect data. Some have suggested that uncertainty caused by the latter increases with decreasing spatial resolution of transect data and sampling densities of 1–7% of the discharge surface area may be required to achieve accurate discharge estimates (e.g., Kubert et al 2006; Li et al ; Mackay et al ).…”
Section: Sustainability Of Szna Source Longevity and Uncertaintymentioning
confidence: 99%
“…Finally, it should be noted that uncertainties inherent in the SZNA rate estimation are difficult to quantify. This reflects uncertainties in all of the measured quantities used in the discharge calculations, especially errors in concentration data (up to 30%; McHugh et al ), errors in hydraulic conductivity measurement (2× to 10×), errors in measurement of hydraulic gradient (2×), differences in results for different data interpolation methods (log, linear, nearest neighbor; 2× to 5×), and uncertainty related to the spatial resolution (sampling density) of transect data. Some have suggested that uncertainty caused by the latter increases with decreasing spatial resolution of transect data and sampling densities of 1–7% of the discharge surface area may be required to achieve accurate discharge estimates (e.g., Kubert et al 2006; Li et al ; Mackay et al ).…”
Section: Sustainability Of Szna Source Longevity and Uncertaintymentioning
confidence: 99%
“…A passive sampler can cover a long sampling period and integrate pollutant concentrations over time. Although compared to conventional monitoring, the use of passive samplers can significantly reduce analytical costs, a validation procedure that includes an assessment of the degree of sampling uncertainty remains a challenge [15,17,[40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%